Serum levels of neuregulin-1 in patients with coronary artery disease: clinical and pathogenetic aspects - E. A. Zakharyan; A. V. Ushakov (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To determine the relationship between the serum level of neu-regulin-1 (NRG-1) and the severity of coronary artery (CA) atherosclerosis and clinical and paraclinical characteristics of patients with coronary artery disease (CAD).Material and methods. The study included 264 people, of which 220 were patients diagnosed with coronary CAD. The patients underwent coronary angiography using the Synergy between Percutaneous Coronary Intervention with TAXUS and Cardiac Surgery (SYNTAX) score and echocardiography. The patients were divided into groups according to SYNTAX score: group 1 — with moderate CA atherosclerosis (≤22 (n=124); group 2 — with severe CA atherosclerosis (23-32) (n=53); group 3 — with extremely severe CA atherosclerosis (≥33) (n=43). Group 4 was represented by healthy volunteers (n=44). All subjects underwent a study of the serum NRG-1 (ng/ml) level. Statistical processing of the results was carried out using Statistica 10.0 software. Differences were considered significant at p<0,05.Results. Significantly higher NRG-1 values were obtained in the control group compared to patients with CAD (p<0,001). An inverse correlation was found between the NRG-1 concentration and the severity of CA atherosclerosis (p<0,001). A decrease in NRG-1 concentration is associated with a high functional class of = heart failure (p<0,01) and low left ventricular ejection fraction (p<0,001). The significance of NRG-1 differences between groups of patients with a history of myocardial infarction (p<0,001), angina pectoris (p<0,01), permanent atrial fibrillation (p<0,01), chronic left ventricular aneurysm (p<0,01) and repeated myocardial infarction (p<0,05) in comparison with patients without these pathologies.Conclusion. The identified correlations between the NRG-1 concentration and CAD, as well as the clinical and paraclinical characteristics of patients, makes it possible to consider NRG-1 as a reliable biomarker of CA and heart failure severity and may form the basis for the development of novel diagnostic approaches.